Development and validation of a quantitative snack and beverage food frequency questionnaire for adolescents - De Cock, Nathalie; Van Camp, John; Kolsteren, Patrick; Lachat, Carl; Huybregts, Lieven; Maes, Lea; Deforche, Benedicte; Verstraeten, Roosmarijn; Vangeel, Jolien; Beullens, Kathleen; Eggermont, Steven; Van Lippevelde, Wendy (Wiley, 2017)
A short, reliable and valid tool to measure snack and beverage consumption in adolescents, taking into account the correct definitions, would benefit both epidemiological and intervention research. The present study aimed to develop a short quantitative beverage and snack food frequency questionnaire (FFQ) and to assess the reliability and validity of thisFFQagainst three 24‐h recalls.Reliability was assessed by comparing estimates of theFFQadministered 14 days apart (FFQ1 andFFQ2) in a convenience sample of 179 adolescents [60.3% male; mean (SD) 14.7 (0.9) years]. Validity was assessed by comparingFFQ1 with three telephone‐administered 24‐h recalls in a convenience sample of 99 adolescents [52.5% male, mean (SD) 14.8 (0.9) years]. Reliability and validity were assessed using Bland–Altman plots, classification agreements and correlation coefficients for the amount and frequency of consumption of unhealthy snacks, healthy snacks, unhealthy beverages, healthy beverages, and for the healthy snack and beverage ratios.Small mean differences (FFQ1 versusFFQ2) were observed for reliability, ranking ability ranged from fair to substantial, and Spearman coefficients fell within normal ranges. For the validity, mean differences (FFQ1 versus recalls) were small for beverage intake but large for snack intake, except for the healthy snack ratio. Ranking ability ranged from slightly to moderate, and Spearman coefficients fell within normal ranges.Reliability and validity of theFFQfor all outcomes were found to be acceptable at a group level for epidemiological purposes, whereas for intervention purposes only the healthy snack and beverage ratios were found to be acceptable at a group level.